Analysis of Reproductive Characters in Hybrid Pig Combination (CLW x CL) x (D x Pn) - Libor Sládek (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2017)
The aim of the experiment was to analyse reproductive characters in hybrid pig combination (CLW x CL) x (D x Pn). These reproductive traits of sows were studied: number of all, live born and weaned piglets, loses from live born piglets till weaning. These influences with an impact on reproductive characters were monitored: order of litter, number of piglets in a litter, birth weight of piglets, influences of sex and litter order on birth weight of piglets. An average number of all born piglets per sow and litter it was 13.25 piglets. From this an average number of live born piglets it was 12.48 piglets per sow and litter and from each litter there was 11.40 of weaned piglets. The highest number of live born piglets was reached in sows on the fourth litter – 14.50 piglets. On eighth and nineth litter fertility decreased to 11.60 and 11.00 piglets. Statistical conclusive difference (P ≤ 0.05) was found between fourth (14.50) and nineth (11.00) litter. Among birth weight in both sexes a statistical conclusive difference (P ≤ 0.05) was found. Higher birth weight (1.46 kg) was found in boars in comparison with gilts (1.40 kg). The highest birth weights in gilts were reached in litters of sows on the second and nineth litters – 1.49 kg and 1.48 kg. Birth weight decreased on tenth litter with average weight of 1.28 kg. The highest birth weight in boars was detected on the seventh litter but on the seventh litter piglets of only one sow were weightened so the result 1.67 kg is not objective. The second highest average birth weight was reached on the third litters – 1.53 kg. On the contrary the lowest average birth weight was on the fourth and tenth litters where boars reached weight of 1.28 and 1.25 kg. Statistical conclusive difference (P ≤ 0.05) was found between the second (1.53 kg) and tenth (1.25 kg) litter.